Ramsey’s theorem and products in the Weihrauch degrees - Arno Pauly (Computability, 2020)
We study the positions in the Weihrauch lattice of parallel products of various combinatorial principles related to Ramsey’s theorem. Among other results, we obtain an answer to a question of Brattka, by showing that Ramsey’s theorem for pairs (RT22) is Weihrauch-incomparable to the parallel product of the stable Ramsey’s theorem for pairs and the cohesive principle (SRT22×COH).